Participatory Management in the Development of a Merdeka Belajar Literacy Culture in Senior High Schools in the Bangka Belitung Islands - Dewi, Indah Kusuma; Rada; Mashar, Ali (Universitas Islam Negeri Raden Intan Lampung, 2026)
Literacy culture is a strategic condition for implementing Merdeka Belajar because independent learning requires students who can read critically, select information ethically, reflect on experience, and communicate ideas responsibly. Yet school literacy programs often remain procedural when planning, role distribution, implementation, and supervision are not managed participatively. This study analyzes how participatory management shapes the development of an independent-learning literacy culture in senior high schools in the Bangka Belitung Islands. This study employed qualitative field research in senior high schools that had implemented the Merdeka Belajar curriculum. Data were collected for 12 months through observation, semi-structured interviews, and documentation involving principals, curriculum leaders, infrastructure leaders, librarians, homeroom teachers, subject teachers, and students. Data were analyzed through data condensation, data display, conclusion drawing, and verification, while credibility was strengthened through source and technique triangulation. The findings show four interconnected management functions. Planning emerged through teacher initiatives and principal facilitation, producing a literacy team, 15-minute reading habituation, reading-corner planning, student literacy ambassadors, and library-based resource development. Organizing distributed responsibilities among the principal, literacy team, curriculum unit, library, homeroom teachers, and students. Implementation established reading routines, journals, library visits, and literacy competitions but was constrained by limited book collections, underused reading corners, and uneven library accreditation. Supervision combined direct monitoring, reading journals, peer reminders, and semester evaluation. The study contributes a participatory literacy management model aligned with Al-Tadzkiyyah's scope on Islamic educational leadership, management, pedagogical innovation, contextual dynamics, and SDG 4-oriented quality education.